A measure of service quality on water in Lepelle-Nkumpi Municipality in the Limpopo Province - Shongwe, Nkosinathi Sipho (My University, 2007)
The residents of Lebowakgomo in Lepelle-Nkumpi Municipality experience numerous inequalities in relation to water services provision. Some of the residents protest towards the inequalities through refusal to pay for the water services. The confrontational non paying residents field questions which the municipality can hardly answer. The problem of refusal to pay is of the magnitude that recently the municipality had to go house-to-house pleading with the inhabitants to pay if the municipality was to continue to provide water services. The specific objectives of this study were three-fold: (1) to determine water service quality using residents’ perceptions on water services in Lebowakgomo, (2) to determine residents’ expectations and perceptions on water services in Lebowakgomo, and (3) to determine the residents’ perceptions on water service quality and customer satisfaction in Lebowakgomo using age, gender, qualification and suburb. A questionnaire comprising five dimensions, namely, tangibles, reliability, assurance, empathy and responsiveness, was compiled to collect data from three suburbs of Lebowakgomo in Lepelle-Nkumpi Municipality. The original sample size was 120, with 9 becoming spoiled due to missing data. The independent variables comprised age, qualification, suburb and gender. Most of the data were analysed for kurtosis and skewness and with the exception of one variable, the rest of the data did not conform to parametric analysis criteria. The major findings of this study indicated overall negative perceptions of residents’ on four dimensions of empathy, reliability, responsiveness and assurance on water service quality which implied that the residents were dissatisfied with the service and called on management to use SERVQUAL as a valid model of assessment to identify areas requiring immediate attention for service improvement. On the other contra positive it was revealed that the municipality was doing well on the tangibles dimension. ix The study recommended use of SERVQUAL in measuring quality of other services within the constitutional competencies of the municipality and further research to investigate age contribution to service quality.
Thesis (MBA.) -- University of Limpopo, 2007
Keywords: Water service quality; Water supply; Water quality -- South Africa -- Limpopo; Water supply -- South Africa -- Limpopo; Municipal water supply; Water supply -- Evaluation